Pengolahan Intrusi Air Laut Menggunakan Sistem Hybrid Multistage Reverse Osmosis: Analisis Tds, Turbiditas, Dan Korelasi Kinerja Proses - Yusuf, Mirza; Hakim, Iqbal Lukman; Hermawan, Andi; Mohammad Syaiful Anwar (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2026)
Clean-water demand in coastal settlements has increased dependence on groundwater and may intensify water-quality deterioration caused by seawater influence, surface runoff, and local hydrogeological conditions. This study evaluates dug-well water quality in the South Depok Coastal area using Total Dissolved Solids (TDS) and turbidity, and examines the relevance of a hybrid multistage reverse osmosis (RO) system for raw-water treatment. Water samples were purposively collected from 10 community wells in January and May 2025. The mean TDS increased from 84.15 mg/L to 171.70 mg/L, while mean turbidity increased from 1.48 NTU to 5.81 NTU. The Pearson correlation between TDS and turbidity was positive, with r=0.74 in January, r=0.60 in May, and r=0.67 for the combined dataset. These results show that higher dissolved-solid concentrations tend to coincide with higher turbidity, although the relationship is affected by well-specific conditions, rainfall, suspended matter, and local hydrogeology. Although all TDS values remained below 500 mg/L, five May samples exceeded the 5 NTU turbidity threshold. A multistage treatment train consisting of sedimentation, multimedia filtration, cartridge filtration, pH-antiscalant conditioning, RO membrane separation, remineralization, and disinfection is therefore recommended to reduce particulate loading and stabilize treated-water quality. Future studies should report stage-by-stage permeate and concentrate data to validate membrane performance quantitatively.